(untitled) (Politeja, 2022)
PROSPECTS FOR REFORM OF THE EUROPEAN UNION’S COMMON SECURITY AND DEFENCE POLICY TO 2025: EU STRATEGIC AUTONOMY? The research objective of the paper is to highlight the prospects for the implementation of the main directions of the reform of the Common Security and Defense Policy (CSDP) of the European Union until 2025. The caesuras of the work are marked by two events: the adoption of the Global Strategy for the Foreign and Security Policy of the European Union by the European Council on 28 June 2016 and the decision of the European Council of 24 March 2022 on the adoption of the Strategic Compass for Security and Defense. First of all, the research hypothesis should be established that the full implementation of CSDP reform, which was initiated with the adoption of the Global Strategy for the Foreign and Security Policy of the European Union, and the resulting projects can significantly strengthen the position of the EU in the international arena. This will lead to the establishment of the European Security and Defense Union and the EU Rapid Reaction Force (5,000 troops) by the end of 2025. However, since many of the planned reform elements have not yet been completed or initiated, much will depend on the political will of individual member state governments, the level of spending on reform implementation by member states and the EU, and the progress of other reforms already underway (including addressing the economic and social consequences of the pandemic crisis and implementing eurozone systemic reform). The following research questions should then be asked: (1) How has the implementation process of the Global Strategy for the European Union’s Foreign and Security Policy gone so far? (2) How has the implementation of new projects (including the European Defense Fund, PESCO, and the Strategic Compass) affected EU-NATO relations? (3) How do selected EU member states assess these projects? (4) To what extent can the project to establish a European Security Council with the participation of Germany, the Netherlands, the United Kingdom and Poland compete with and usefully complement the EU Strategic Compass project? The first part of the analysis presents the implementation process of the Global Strategy for the Foreign and Security Policy of the European Union until 2022. The second part analyzes the goals, priorities, and assumptions of the Strategic Compass, the implementation of which is intended to lead the EU to strategic autonomy by 2030.